Assessment of diastase levels in different floral honey from Oromia region, Ethiopia - Deressa Kebebe Meskele; Teferi Damto; Meseret Gemeda; Gemechis Laggase (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2022)
Diastase is an enzyme that is found naturally in honey and degrades over time, especially when exposed to heat. Diastase can be used to indicate the age and exposure of honey to heat. However, they play a very significant role in honey quality. This study aimed to assess the diastase levels of different floral honey in potential areas of the Oromia region. In this study diastase activity, free acidity, and pH contents of different floral kinds of honey of potential areas in the Oromia region of Ethiopia were investigated based on the IHC- 2009- method. The honey pollen spectra were also characterized. When compared to other flora honey collected from the study area, the diastase activity of Erica arborea honey revealed significantly different (p < 0.05). It ranged from 4.61 ± 1.50 to 12.75 ± 4.78 Schade unit. The results of the pH value and free acidity analyses test demonstrated that the honey samples used in this investigation were fresh which ranged from 3.22 ± 0.13 to 4.17 ± 0.97 and 22.43 ± 6.37 to 35.10 ± 10.51 meq/kg honey, respectively.  Honey bees' geographical race, location and harvesting time affected diastase activities. However, it was not possible to identify the real factor influencing its diastase activities which needs further study at different agroecologies for different floral kinds of honey of the country.